Analisis efektifitas penerapan perencanaan pajak untuk meminimalkan beban pajak perusahaan (Studi pada PT Andalan Bisturi Pratama) - Rofita, Maula; Saman, Saman (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
<p class="MsoNormal" style="margin-bottom: .0001pt; text-align: justify; line-height: normal; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt;">This study aims to evaluate whether the application of taxation has been implemented effectively and can minimize the tax burden. Data collection techniques were carried out by means of interviews and documentation. The analysis used is quantitative. From the results of the study, it was found that the application of tax planning carried out by the company was not effective because in the recognition of costs it was still using the accounting basis and not in accordance with the tax law. Â <!–[if gte vml 1]> <v:shape id="Picture_x0020_10" o:spid="_x0000_s1028" type="#_x0000_t75" style=’position:absolute;left:0;text-align:left;margin-left:160.2pt; margin-top:.25pt;width:294.4pt;height:42pt;z-index:-251659264;visibility:visible; mso-wrap-style:square;mso-width-percent:0;mso-height-percent:0; mso-wrap-distance-left:9pt;mso-wrap-distance-top:0;mso-wrap-distance-right:9pt; mso-wrap-distance-bottom:0;mso-position-horizontal:absolute; mso-position-horizontal-relative:page;mso-position-vertical:absolute; mso-position-vertical-relative:text;mso-width-percent:0;mso-height-percent:0; mso-width-relative:page;mso-height-relative:page’> <![endif]–><!–[if !vml]–> <!–[endif]–><!–[if gte vml 1]><v:shape id="Picture_x0020_9" o:spid="_x0000_s1027" type="#_x0000_t75" style=’position:absolute;left:0; text-align:left;margin-left:470.8pt;margin-top:83.2pt;width:42.8pt;height:53.2pt; z-index:-251658240;visibility:visible;mso-wrap-style:square; mso-width-percent:0;mso-height-percent:0;mso-wrap-distance-left:9pt; mso-wrap-distance-top:0;mso-wrap-distance-right:9pt; mso-wrap-distance-bottom:0;mso-position-horizontal:absolute; mso-position-horizontal-relative:page;mso-position-vertical:absolute; mso-position-vertical-relative:page;mso-width-percent:0;mso-height-percent:0; mso-width-relative:page;mso-height-relative:page’> <![endif]–><!–[if !vml]–> <!–[endif]–><!–[if gte vml 1]><v:shape id="Picture_x0020_8" o:spid="_x0000_s1026" type="#_x0000_t75" style=’position:absolute;left:0; text-align:left;margin-left:92.8pt;margin-top:83.2pt;width:54pt;height:54pt; z-index:-251657216;visibility:visible;mso-wrap-style:square; mso-width-percent:0;mso-height-percent:0;mso-wrap-distance-left:9pt; mso-wrap-distance-top:0;mso-wrap-distance-right:9pt; mso-wrap-distance-bottom:0;mso-position-horizontal:absolute; mso-position-horizontal-relative:page;mso-position-vertical:absolute; mso-position-vertical-relative:page;mso-width-percent:0;mso-height-percent:0; mso-width-relative:page;mso-height-relative:page’> <![endif]–><!–[if !vml]–> <!–[endif]–>